Sex difference in the sensitivity of cardiac mitochondrial permeability transition pore to calcium load - Milerová, Marie; Drahota, Zdeněk; Chytilová, Anna; Tauchmannová, Kateřina; Houštěk, Josef; Ošťádal, Bohuslav (Molecular and cellular biochemistry, 2016)
Most of the experimental studies have revealed that female heart is more tolerant to ischemia/reperfusion (I/R) injury as compared with the male myocardium. It is widely accepted that mitochondrial dysfunction, and particularly mitochondrial permeability transition pore (MPTP) opening, plays a major role in determining the extent of cardiac I/R injury. The aim of the present study was, therefore, to analyze (i) whether calcium-induced swelling of cardiac mitochondria is sex-dependent and related to the degree of cardiac tolerance to I/R injury and (ii) whether changes in MPTP components-cyclophilin D (CypD) and ATP synthase-can be involved in this process. We have observed that in mitochondria isolated from rat male and female hearts the MPTP has different sensitivity to the calcium load. Female mitochondria are more resistant both in the extent and in the rate of the mitochondrial swelling at higher calcium concentration (200 µM). At low calcium concentration (50 µM) no differences were observed. Our data further suggest that sex-dependent specificity of the MPTP is not the result of different amounts of ATP synthase and CypD, or their respective ratio in mitochondria isolated from male and female hearts. Our results indicate that male and female rat hearts contain comparable content of MPTP and its regulatory protein CypD; parallel immunodetection revealed also the same contents of adenine nucleotide translocator or voltage-dependent anion channel. Increased resistance of female heart mitochondria thus cannot be explained by changes in putative components of MPTP, and rather reflects regulation of MPTP function.
Keywords: krysa rodu Rattus; Animals; Mitochondrial Membrane Transport Proteins; Rats; Sex Factors; srdeční mitochondrie; Female; mužské pohlaví; vápník; zvířata; Calcium; Male; sexuální faktory; transportní proteiny mitochondriální membrány; Mitochondria, Heart; ženské pohlaví